Perbandingan Kecukupan Asi Ibu Menyusui Antara Konsumsi Ekstrak Daun Kelor dengan Konsumsi Ekstrak Biji Fenugreek - Nur Khasanah; Anita Liliana; Claresta Jessy Widia Sandra (HEALTH CARE : JURNAL KESEHATAN, 2021)
Nutrition Fulfillment for infants aged 0-6 months is essential, it can only be obtained through exclusive breastfeeding. The extent of exclusive breastfeeding coverage is influenced by the mothers’ nutritional adequacy. Breastfeeding mothers need an additional 400-500 kcal of nutrients per day. In addition to high-calorie foods, mothers also need additional nutritional content that can increase breast milk production, such as lactogogum and flavonoids contained in Moringa leaves and fenugreek seeds. The potential of abundant natural resources with extraordinary benefits such as the benefits of Moringa leaves and fenugreek seeds are not yet known by the public, including its benefits in increasing breast milk production. This study aims to determine the difference in breast milk adequacy between mothers who consume Moringa leaf extract (moringa oleifera) and mothers who consume fenugreek seed extract (Trigonella foenum-graecum) in ​​‘Linggang Bigung’ Community Health Center work area. This research has a quasi-experimental format with a post-test-only without control group design. This study involves 32 post-partum mothers as samples. The research data is collected using a non-probability sampling with a purposive sampling technique. Bivariate analysis used in this study is Two Way Anova. Breast milk adequacy is found in 15 respondents in the Moringa leaf extract group (93.75%), while in the fenugreek seed extract group, 14 respondents (87.5%). There is no significant difference between the effects of Moringa leaf extract and fenugreek seed extract on breast milk adequacy in breastfeeding mothers in Linggang Bigung Community Health Center work area, with a significance value in the results showing p = 0.559>0.05.